Coordination of Expectations in Asset Pricing Experiments - Cars Hommes; Joep Sonnemans; Jan Tuinstra; Henk van de Velden (Tinbergen Institute, 2003)
We investigate expectation formation in a controlled experimental en-vironment. Subjects are asked to predict the price in a standard asset pricingmodel. They do not have knowledge of the underlying market equilibrium equa-tions, but they know all past realized prices and their own predictions. Aggregatedemand of the risky asset depends upon the forecasts of the participants. The real-ized price is then obtained from market equilibrium with feedback from individualexpectations. Each market is populated by six subjects and a small fraction of fun-damentalist traders. Realized prices differ significantly from fundamental values.In some groups the asset price converges slowly to the fundamental price, in othergroups there are regular oscillations around the fundamental price. Participantscoordinate on a common prediction strategy. The individual prediction strategiescan be estimated and correspond, for a large majority of participants, to simplelinear autoregressive forecasting rules.
Keywords: C91; C92; D84; G12; G14; 330; experimental economics; expectations; asset pricing; coordination.; CAPM; Erwartungstheorie; Test